ANALISIS FAKTOR YANG MEMPENGARUHI MANAJEMEN PAJAK DENGAN INDIKATOR TARIF PAJAK EFEKTIF (ETR) PADA PERUSAHAAN LQ45 YANG TERDAFTAR DALAM BURSA EFEK INDONESIA TAHUN 2010-2012 - Septi Imelia; Zirman -; Rusli - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research to analyze of factors affect the tax management with indicators of effective tax rate on LQ45 companies listed in Indonesia Stock Exchange for years 2010-2012. There are several factors used include size, leverage, return on assets, inventory intensity, fixed asset intensity, taxation facilities and independent commissioners. This purpose of this study is to empirically examine whether the size, leverage, profitability, inventory intensity, fixed asset intensity, taxation facilities and independent commissioners affect the tax management. The sample of this research of 19 LQ45 companies listed in Indonesian Stock Exchange of years 2010-2012. Determination of sample was made by applying purposive sampling. Analysis tool used multiple linear regression with F test, t test and the coefficient of determination was conducted using SPSS version 17 for windows. The result showed that the variable size, leverage, profitability, inventory intensity, fixed asset intensity, taxation facilities and independent commissioners affect significantly simultaneously (F test) tax management. From the result of the analysis of partially (t test) the variable size, profitability, inventory intensity, fixed asset intensity did not affect significantly to tax management, while the leverage, taxation facilities and independent commissioners influential significantly to tax management. The result of the coefficient determination showed 34% independent variable affect to dependent variable and 66% can be explain with the other variables.Keywords: Tax Management, Effective Tax Rate, Size, Leverage, Profitability, Inventory Intensity, Fixed Asset Intensity, Taxation Facilities, Independent Commissioners